2016
DOI: 10.3341/kjo.2016.30.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Posterior Subtenon Triamcinolone Acetonide Injection on Diabetic Macular Edema Refractory to Intravitreal Bevacizumab Injection

Abstract: PurposeTo evaluate the effects of posterior subtenon triamcinolone acetonide injection on refractory diabetic macular edema (DME) after intravitreal bevacizumab (IVB) injection failure.MethodsPatients with DME and central subfield thickness (CST) >300 µm who did not respond to IVB injections were retrospectively included. Specifically, we enrolled patients who were diagnosed with refractory DME and who experienced an increase in CST after 1 to 2 IVB injections or no decrease after ≥3 consecutive IVB injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…Responsive group was defined as patients who achieved CST < 300μm after 3IVBs with or without dexamethasone implant and refractory group was defined as patients who showed CST ≥ 300μm even after both treatments (Fig 1). [21, 22] We followed all the patients until 6month after initial treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Responsive group was defined as patients who achieved CST < 300μm after 3IVBs with or without dexamethasone implant and refractory group was defined as patients who showed CST ≥ 300μm even after both treatments (Fig 1). [21, 22] We followed all the patients until 6month after initial treatments.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Lazic et al 69 published significant improvements in central foveal thickness and visual acuity in 16 eyes of 15 patients with refractory DME following three anti-VEGF injections who then underwent injection of DEX implant. In addition, Kim et al 71 reported on 40 eyes of 34 patients with persistent DME despite undergoing previous bevacizumab injections that received 20 mg of posterior subtenon TA. At 2 months, the mean central retinal thickness had decreased by 108 μm while the logMAR vision had improved by 0.06.…”
Section: Corticosteroids In the Eye: Clinical Considerationsmentioning
confidence: 99%
“…The sub-Tenon injection of triamcinolone acetonide (20 mg) was found to effectively inhibit VEGF and reduce the average macular thickness from 476 µm to 368 µm after 2months treatment. No serious complications were reported [176].…”
Section: Sub-tenon Injectionmentioning
confidence: 90%